Pengaruh Kinerja Keuangan Terhadap Harga Saham (Studi Empiris pada Perusahaan yang Terdaftar di Jakarta Islamic Index Tahun 2021-2024) - Nur Hidayat; Agus Solikhin; Arfah .; Rico Wijaya Z (Journal of Islamic Banking, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on the stock prices of companies listed on the Jakarta Islamic Index (JII) for the 2021–2024 period. This study uses secondary data in the form of annual financial reports obtained from the Indonesia Stock Exchange (IDX). The study population consists of 16 companies consistently listed on the JII during the study period. The sampling technique was carried out using a purposive sampling method, resulting in 64 observational data. The analysis method used is panel data regression with the help of the EViews 12 application. The Chow and Hausman tests indicate that the appropriate model is the Random Effect Model (REM). The results show that the ROA variable has a positive and significant effect on stock prices. Meanwhile, the CR, DER, and TATO variables do not have a significant effect on stock prices. The simultaneous test (F test) shows that ROA, CR, DER, and TATO together have a significant effect on JII stock prices.